Evidence for the involvement of VAR2CSA in pregnancy-associated malaria. - Salanti, A; Dahlbäck, M; Turner, L; Nielsen, M; Barfod, L; Magistrado, P; Jensen, A; Lavstsen, T; Ofori, M; Marsh, K; Hviid, L; Theander, T (2004)
In Plasmodium falciparum-endemic areas, pregnancy-associated malaria (PAM) is an important health problem. The condition is precipitated by accumulation of parasite-infected erythrocytes (IEs) in the placenta, and this process is mediated by parasite-encoded variant surface antigens (VSA) binding to chondroitin sulfate A (CSA). Parasites causing PAM express unique VSA types, VSAPAM, which can be serologically classified as sex specific and parity dependent. It is sex specific because men from malaria-endemic areas do not develop VSAPAM antibodies; it is parity dependent because women acquire anti-VSAPAM immunoglobulin (Ig) G as a function of parity. Previously, it was shown that transcription of var2csa is up-regulated in placental parasites and parasites selected for CSA binding. Here, we show the following: (a) that VAR2CSA is expressed on the surface of CSA-selected IEs; (b) that VAR2CSA is recognized by endemic plasma in a sex-specific and parity-dependent manner; (c) that high anti-VAR2CSA IgG levels can be found in pregnant women from both West and East Africa; and (d) that women with high plasma levels of anti-VAR2CSA IgG give birth to markedly heavier babies and have a much lower risk of delivering low birth weight children than women with low levels.